Humanization of the learning environment - 2022: Results of the international forum - Marina N. Burmistrova (Saratov State University, 2022)
The results of the International Forum "Humanization of the Learning Environment" have been summed up. The Forum was held on March 1-2, 2022. Saratov State University hosted it. The purpose of the Forum was to identify and discuss the role of a young teacher in the transformation of the educational system.